Cortical excitability and rest activity properties in patients with depression. - Salustri C; Tecchio F; Zappasodi F; Bevacqua G; Fontana M; Ercolani M; Milazzo D; Squitti R; Rossini PM (Journal of Psychiatry & Neuroscience, 2007)
OBJECTIVE: Results of recent studies suggest a link between neuronal excitatory or inhibitory unbalance and depression. To investigate this relation, we studied the rest activity and the cortical excitability of the cerebral areas dedicated to hand control in 12 patients with depression. METHODS: Brain activity was recorded from the Rolandic region in both hemispheres of 12 depression patients and 11 control subjects by means of magnetoencephalography. We studied cortical excitability by focusing on the M20 and M30 components of the magnetic fields evoked by a stimulation of the median nerve. RESULTS: Parietal rest rhythms showed greater total power in patients than in control subjects. In particular, the patient's parietal alpha was higher in the right than in the left hemisphere. Primary sensory cortex excitability, expressed by the M20, appeared significantly reduced in patients with depression, but was still higher in the right than in the left hemisphere. The M30 also appeared reduced, and this reduction was significantly correlated with both depression severity and global illness. CONCLUSIONS: The patients studied were not completely drug free. For this reason, it is impossible to rule out the possibility that our results are an effect of drug assumption. Nevertheless, since all patients were well below the drugs' steady state levels when the data were recorded, the behaviour of M20 and M30 and their relation with the patients' clinical pictures suggest that an unbalance of the excitatory or inhibitory cortical activity, and especially a potentiation of the parietal afferent to the motor cortex, may be significant hallmarks of depression.